Conscious self-regulation as a resource for success in the Russian language in students with different levels of intelligence - I.N. Bondarenko; A.M. Potanina; V.I. Morosanova (Экспериментальная психология, 2020)
The article offers a new view of the assessment of success in the Russian language. Four language competencies are used as its indicators: Language Proficiency, Literacy, Word Structure, and Sentence Structure. The diagnosis is based on the principle of mastering the norms of the language. The study aims to identify regulatory and intellectual predictors of this success. Two hundred eighty-six students in grades 7 and 9 (50.3% girls) completed the questionnaire assessing the level of conscious self-regulation of V. I. Morosanova. In addition, they carried out Raven’s test and two tasks on the language competence assessment. The results showed that gender, age, conscious self-regulation and intelligence significantly influences success in Russian. It is important to note that the contribution of self-regulation significantly exceeded the contribution of intelligence in adolescence. We conducted a similar analysis of a sample divided by gender. The results shed light on the resources for increasing success in Russian for girls and boys. The development of intellectual abilities is promising for girls; the level of intelligence and conscious self-regulation (and above all, the Modeling process), are essential for boys.